Diagnostic of a maxillary anterior double tooth and management by a mixed endodontic and surgical approach: a case report - Chim Vanessa; Grosborne Matthieu; Laccourreye Paul; Valenti Agathe; Bayet Kinz (Journal of Oral Medicine and Oral Surgery)
Introduction: The purpose of this case report was to discuss the diagnosis and management of a rare dental anomaly involving a maxillary central incisor with a bifid crown, treated through a combined endodontic and surgical approach. Dental anomalies, such as gemination and fusion, can lead to irregularities in tooth size, structure, and number, which can pose challenges in diagnosis and careful consideration for effective management. Observation: A 13-year-old patient sought consultation for aesthetic and orthodontic concerns related to the double tooth (DT). Despite the complexity of the malformation, a conservative mixed endodontic and surgical approach was chosen after multidisciplinary discussion. The patient underwent endodontic treatment followed by crown resection and gingival plastic surgery. Post-operative follow-up showed satisfactory results. Conclusion: This case report emphasizes the challenges in DT diagnostic and the importance of a multidisciplinary approach. Various treatment modalities were explored, highlighting the lack of standardized guidelines and the importance of individualized care.